Cloning of myoglobin (Mb) gene of M. longissimus dorsi and effects of iron glycine on its expression in weanling pigs - MA Wen-qiang; FENG Jie; XU Zi-rong; WANG Yi-zhen; LIU Jian-xin (浙江大学学报. 农业与生命科学版, 2009)
The experiment was conducted to investigate cloning of myoglobin (Mb) gene of M. longissimus dorsi and effects of iron glycine on its expression in weanling pigs. Genome RNA was extracted from M. longissimus dorsi of swine and amplified using RT-PCR. A DNA fragment about 335 bp in length was obtained and the PCR product was cloned into pGEM-T Easy vector. The Mb gene was isolated and sequenced from the screened positive clones. Result of sequence analysis shows that this fragment was the partial sequence of Mb cDNA and coded 111 amino acid residues. The gene homology of the obtained fragment was up to 99% compared with that of reported Mb gene sequence in the adipose of porcine. Based on the Mb gene clone, an optimal semi-quantitative RT-PCR method was successfully constructed. Twenty-four piglets (Duroc × Landrace × Yorkshire) were used to determine Mb mRNA expression after 35 days treated with iron glycine (0, 30, 60, 90, 120 mg·kg-1). Results show that 60, 90 or 120 mg·kg-1 iron glycine could increase the Mb mRNA expression obviously, which were improved by 97.35%, 108.87% and 86.17% (P<0.05), respectively. It was indicated that iron glycine could affect meat color by regulating Mb mRNA expression.